Information, Disinformation, and the Authority of Knowledge in the Age of Babel - Gordon, Mordechai (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2025)
This paper explores some of the perils to American democracy in the age of the Internet, social media, and the filtered bubbles that its citizens inhabit. I open my analysis by revisiting the myth of the Tower of Babel in order to reflect on the insights that can be gleaned for the present state of disinformation. Then I turn to an examination of the notions of polarization and structural stupidity, while tying them to the distinction that C. Thi Nguyen makes between epistemic bubbles and echo chambers. I then argue that the insights of the myth of the Tower of Babel can take us only so far and that an adequate understanding of the current state of affairs in the United States needs to consider the crisis in the authority of knowledge. I base my argument on some insights of philosophers Walter Lippmann and José Ortega y Gasset, who were both concerned about the role of private citizens and the public in the life of a democracy. I conclude this paper by discussing various positions that philosophers of education can take in the age of Babel, while advocating for the need to adopt a probing stance.